1990
DOI: 10.1002/food.19900341028
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinämie und B‐Zellproliferation in postnatal mit L‐Glutamat behandelten Ratten

Abstract: Development of hyperinsulinemia was investigated which appeared late in the obese state in rats postnatally treated with L-glutamate. Insulin concentrations were estimated in the blood plasma of the caval and portal vein, and morphometric and immunohistochemical measurements of cells in the islets of Langerhans were performed, and also glucose tolerance tests. Not earlier than at 3 months hyperinsulinemia is shown in glutamate obese rats (GOR) in the peripheral blood plasma. Also in the portal blood plasma the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In contrast to other animal models of obesity, accumulation of triglycerides is not accompanied by peripheral hyperinsulinemia (Pöge et al, 1990).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast to other animal models of obesity, accumulation of triglycerides is not accompanied by peripheral hyperinsulinemia (Pöge et al, 1990).…”
Section: Introductionmentioning
confidence: 80%
“…From these findings it may be concluded that hyperinsulinemia of glutamate-induced obese rats can not be attributed to diminished organ specific insulin binding. More likely an age dependent increase in insulin secretion of n-cells of pancreas (Pöge et al, 1990) may cause the development of peripheral hyperinsulinemia. Despite of hyperinsulinemia and unchanged insulin binding of obese rats altered insulin sensitivity is possible may be as a result of postreceptor defects.…”
Section: Discussionmentioning
confidence: 99%